2002
DOI: 10.1097/00002030-200203290-00002
|View full text |Cite
|
Sign up to set email alerts
|

Indinavir acutely inhibits insulin-stimulated glucose disposal in humans: A randomized, placebo-controlled study

Abstract: A single dose of indinavir acutely decreases total and non-oxidative insulin-stimulated glucose disposal during a euglycemic, hyperinsulinemic clamp. Our data are compatible with the hypothesis that an acute effect of indinavir on glucose disposal in humans is mediated by a direct blockade of GLUT-4 transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
152
3
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(177 citation statements)
references
References 34 publications
(40 reference statements)
14
152
3
8
Order By: Relevance
“…In contrast to some other PIs, 8,10,11 no clinically significant changes were seen in insulin sensitivity in either the DRV/r or ATV/r arm of this study. Treatment with indinavir and treatment with LPV/r have both been associated with the development of insulin resistance in healthy subjects [9][10][11] ; however, other studies have demonstrated that LPV/r does not affect insulin sensitivity in healthy subjects.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…In contrast to some other PIs, 8,10,11 no clinically significant changes were seen in insulin sensitivity in either the DRV/r or ATV/r arm of this study. Treatment with indinavir and treatment with LPV/r have both been associated with the development of insulin resistance in healthy subjects [9][10][11] ; however, other studies have demonstrated that LPV/r does not affect insulin sensitivity in healthy subjects.…”
Section: Discussioncontrasting
confidence: 92%
“…In contrast to some other PIs, 8,10,11 no clinically significant changes were seen in insulin sensitivity in either the DRV/r or ATV/r arm of this study. Treatment with indinavir and treatment with LPV/r have both been associated with the development of insulin resistance in healthy subjects [9][10][11] ; however, other studies have demonstrated that LPV/r does not affect insulin sensitivity in healthy subjects. 12,13 Atazanavir has generally had little effect on insulin sensitivity in previous trials of HIV-negative subjects, 10,12 and switching from other PI-based therapies to ATV/r has been shown to improve insulin sensitivity in HIV-1-infected subjects.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…17 Moreover, the incidence of insulin resistance in HIV-positive patients is significantly higher in HPI-treated patients than in patients treated with NRTIs or NNRTIs, 18 even when one considers related factors such as demography and virology. 19 Furthermore, HPIs have been shown to induce insulin resistance in seronegative patients and in animal models, [20][21][22][23] implying a clear link between HPI use and insulin resistance. However, the underlying precise mechanisms have yet to be elucidated.…”
Section: Insulin Resistance and Hiv Protease Inhibitors (Hpis)mentioning
confidence: 99%
“…The studies reviewed above suggest that the effects of HPI occur downstream in the insulin signalling pathway in 3T3-L1 adipocytes, in rats and humans, 21,22,24 possibly at the level of PKB/Akt activation and beyond. However, there is evidence that HPIs possibly act at a more proximal level of the insulin signalling pathway.…”
Section: Do Hpis Impair the Proximal Steps Of The Insulin Signalling mentioning
confidence: 99%